Risk of pancreatic cancer after cholecystectomy: a cohort study in Sweden. Issue 5 (1st November 2001) - Ye, W; Lagergren, J; Nyrén, O; Ekbom, A
Abstract : BACKGROUND: Although some experimental studies have indicated that cholecystectomy may increase the risk of pancreatic cancer, data from epidemiological studies are conflicting. AIMS: We conducted a register based retrospective cohort study to explore the relationship between cholecystectomy and pancreatic cancer. SUBJECTS: The cohort included 87 263 men and 181 049 women with a documented cholecystectomy for cholelithiasis between 1965 and 1997. METHODS: By record linkage to the nationwide and virtually complete registers of Cancer, Emigration, and Causes of Death, the cohort was followed up until the occurrence of any cancer, emigration, death, or the end of follow up, 31 December 1997, whichever came first. Relative risk was estimated by standardised incidence ratio (SIR) using the Swedish nationwide sex, age, and calendar year specific cancer incidence rates as reference. RESULTS: During the period of observation, 1053 cases of pancreatic cancer were found, among which 231 (22%) occurred within 12 months after operation. After excluding cases and person years accrued during the first two years of follow up, we observed a non-significant 6% excess risk for pancreatic cancer (95% confidence interval (CI) −2 to 14%). The relative risk did not increase with increasing follow up duration, with a SIR equal to 0.98 (95% CI 0.79–1.20) 20 years or more after operation. Patients with a comorbidity of diabetes or chronic pancreatitis had higher relative risks (SIR=1.79, 95% CI 1.39–2.28; SIR=3.17, 95% CI 1.37–6.24, respectively). After excluding patients with recorded diabetes or chronic pancreatitis, the relative risk was close to unity (SIR=1.01, 95% CI 0.94–1.09). CONCLUSIONS: Our findings do not support the hypothesis that cholecystectomy increases the subsequent risk of pancreatic cancer.